2005
DOI: 10.1097/00002030-200501030-00005
|View full text |Cite
|
Sign up to set email alerts
|

Circulating proviral HIV DNA and HIV-associated dementia

Abstract: These findings suggest a potentially important association between circulating provirus and HAD.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

5
126
1

Year Published

2007
2007
2021
2021

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 105 publications
(132 citation statements)
references
References 51 publications
5
126
1
Order By: Relevance
“…Cells of the monocyte and macrophage lineage may represent another mechanism for viral persistence. These cells are among the cells infected early upon exposure to HIV (11), and the presence of CCR5-utilizing "macrophage-tropic" forms of HIV in the plasma of essentially all newly infected individuals is consistent with the notion that macrophages represent an early target for HIV infection (12)(13)(14)(15). In contrast to CD4 T cells which die with effective HIV replication, macrophages are resistant to the cytopathic effect of the virus.…”
supporting
confidence: 75%
“…Cells of the monocyte and macrophage lineage may represent another mechanism for viral persistence. These cells are among the cells infected early upon exposure to HIV (11), and the presence of CCR5-utilizing "macrophage-tropic" forms of HIV in the plasma of essentially all newly infected individuals is consistent with the notion that macrophages represent an early target for HIV infection (12)(13)(14)(15). In contrast to CD4 T cells which die with effective HIV replication, macrophages are resistant to the cytopathic effect of the virus.…”
supporting
confidence: 75%
“…Shiramizu et al reported isolating CD14 high CD16 ϩ monocytes from the peripheral blood of five HIV-1 infected individuals, three of whom were clinically defined as having HIV-related dementia. These cells harbored HIV-1 DNA in all five donors, although the infection of CD14 high CD16 Ϫ monocytes was not examined (72).…”
Section: Discussionmentioning
confidence: 99%
“…5,6 HIV DNA within the activated CD141 monocyte subset of PBMC correlates with neurocognitive decline. 5,7 We have linked elevated PBMC HIV DNA to cortical thinning 8 but the relationship of HIV DNA to brain structure has not otherwise been explored.…”
mentioning
confidence: 99%
“…HIV DNA assay was carried out as detailed elsewhere, with low intra-assay and interassay variability shown by mean coefficients of variation of 1.1% and 1.4%, respectively. 7 We analyzed copy numbers of each sample gene (HIV gag and b-globin) against standard curves, and determined the HIV DNA copy number per 1 3 10 6 cells. ).…”
mentioning
confidence: 99%